EFFECT OF SUBMERGED FERMENTATION ON THE ANTIBACTERIAL AND ANTIOXIDANT PROPERTIES OF AQUEOUS EXTRACTS OBTAINED FROM VOACANGA AFRICANA STAPF SEED - VO, OYETAYO; OR, ITIOLA (Innovare Journal of Life Sciences, 2023)
Voacanga africana Stapf which belongs to the family, Apocynaceae is among useful medicinal plants of West Africa. The present study investigates the antibacterial and antioxidant properties of aqueous extracts obtained from raw and fermented V. africana. One portion of V. africana was subjected to submerged fermentation for 7 days. Aqueous extracts of the raw and fermented samples of V. africana were obtained using standard methods. Antibacterial effect of the aqueous exracts was assessed by agar well diffusion while a battery of antioxidant test which include DPPH scavenging, ABTS, and Fe2+ chelation was employed. The bioactive compounds present in the extract were assessed using gas chromatography-mass spectrophotometer. Extract obtained from the fermented seed of V. africana had good antimicrobial effect with zones of inhibition ranging from 4.67 to 22.00 mm. Aqueous extract obtained from fermented V. africana exhibited better antioxidant capacity with DPPH scavenging effect being the highest (27.93) when compared with extract obtained from raw V. africana. Bioactive compounds such as Eicosane, 1,14-Dibromotetradecane, 7-Oxodehydroabietic acid, oleic acid and so on were present in the aqueous extract obtained from fermented V. africana. Data gathered from this study revealed that fermentation enhances the antimicrobial and anoxidant properties of V. africana. The presence of bioactive compounds in the aqueous extract of V. africana indicates that it could be a good source of natural antimicrobial and antioxidant compounds for the improvement of human health.